Preventing the Exploitation of Indonesian Migrant Workers by Illegal Companies - Endeh Suhartini; Defisa; Hidayat Rumatiga; Andri Brawijaya; Yahya Habib (Ann Publisher, 2025)
Exploitation is the excessive, unfair, and unlawful use or exploitation of resources, labor, and other resources for personal or group gain. Legal protection for Indonesian migrant workers employed through AKAN or AKAD must comply with applicable law to ensure legal certainty. Exploitation prevention is achieved by ensuring Indonesian migrant workers' understanding of the procedures and companies sending them. Indonesian migrant workers must work through authorized companies and comply with applicable legal procedures. This study aims to determine the form of legal protection for Indonesian Migrant Workers and recommend efforts that can be made to prevent the exploitation of Indonesian Migrant Workers. This research uses a normative juridical approach, which focuses on analyzing legal texts, legal norms, and applicable legal rules. The research concludes as follows: Preventing the exploitation of Indonesian migrant workers who will enter employment through AKAN (Inter-Country Work Agreements) and AKAD (Inter-Regional Work Agreements) requires Indonesian migrant workers to be more careful in selecting companies that will send them as Indonesian migrant workers and to understand the provisions of laws and regulations related to employment law, as they regulate their rights and obligations, thereby ensuring legal certainty. This research is crucial for developing legal protection for Indonesian migrant workers. It serves as a scientific study that can be referenced by other researchers conducting similar research. It can also serve as a resource for the public to learn about Indonesian labor law.